Evaluation of Physicians’ Knowledge and Anxiety Levels About Inherited Metabolic Diseases: Survey Study - Enver, Ece Öge; Yılmaz, Bilal (Cerrahpaşa Medical Journal, 2025)
Objective: Inherited metabolic disorders (IMDs) are rare genetic disorders with complex clinicalpresentations. Due to their rarity and limited presence in medical education, there is a lack of knowledge and increased anxiety among physicians in the management of these diseases. This study aims to evaluate the knowledge and anxiety levels of physicians about IMDs and to determine the factors affecting their professional competence. Method: A cross-sectional survey was conducted with the participation of 83 physicians across Türkiye. Participants completed an online questionnaire assessing demographic data, knowledge of IMDs, and anxiety about these diseases. The data were analyzed using statistical methods such as t-tests and chisquare tests. Results: The mean knowledge level of physicians was 5.6 ± 2.1 on a 10-point scale, indicating that they had basic knowledge but lacked advanced knowledge. The mean anxiety score was 5.3 ± 2.4, and the most common cause of anxiety was reported as lack of knowledge by 60.2%. It was observed that physicians who saw IMD patients less frequently perceived their level of knowledge to be higher than it was due to their inability to adequately recognize the complexity of these diseases. Although the presence of a metabolic specialist in the institution increased self-confidence, it did not have a significant effect on knowledge and anxiety levels. Conclusion: This study highlights the importance of systematic educational programs in IMD management by revealing physicians’ lack of knowledge and increased anxiety levels. Interactive case-based learning, preparation of national guidelines, and interdisciplinary collaboration are critical to increasing knowledge and improving patient outcomes. Cite this article as: Enver EÖ, Yılmaz B. Evaluation of physicians’ knowledge and anxiety levels about inherited metabolic diseases: survey study. Cerrahpaşa Med J. 2025, 49, 0006, doi:10.5152/cjm.2025.25006.